El derecho del trabajo como rehabilitación social para los privados de libertad del Centro de Rehabilitación Social del cantón Guaranda año 2022. - Escobar Naranjo, Carlos Elian (2024)
In Ecuador, all prisoners (PPLS) remain within a constant free time without developing any type of activity, so it is important to apply the work and in this way the PPLS are dedicated to carpentry, locksmithing, and crafts activities, among others, with the aim that they do not participate in the formation of criminal gangs and improve social relations, making better use of time in prison, this will prevent the proliferation of any kind of conflict. The research is carried out from a mixed approach, using quantitative-qualitative, compiling reliable data on the research problem and subsequently interpreting said information; As a type of research, the explanatory, descriptive, bibliographic and field research will be applied, as research techniques, the interview and survey were used, which were used as information collection mechanisms in the CRS of the Guaranda Canton. It turns out that work is not guaranteed in the prison centers of Ecuador, which prevents the PPLS from being able to have true rehabilitation, therefore being able to be reincorporated into society in an optimal way and not repeat the commission of criminal acts. The application of work in prison centers will be feasible when the Central Government carries out state actions aimed at strengthening the rehabilitation of PPLS. Keywords: Prison crisis, Public policies, Rehabilitation, Social reintegration, Job.